THE ROLE OF ARTIFICIAL INTELLIGENCE IN DENTOMAXILLOFACIAL RADIOLOGY – A NARRATIVE REVIEW - DHARSHINI S, DR PRIYA; ASWATH M.D.S, DR NALINI; R M.D.S, R SANKAR NARAYANAN; HAZEEN K, JUMAANA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Artificial intelligence (AI) is the ability of a machine to mimic human behaviour and intelligence in order to carry out particular tasks.[1] Intelligence is the explicit capacity to find solutions to particular issues as well as the intrinsic capacity to discover answers to novel challenges and hence AI is defined as an artificial set-up that is able to learn new problem-solving techniques and solve existing ones. This implies that the object must be able to sense its surroundings , search for patterns and recognize them, plan and carry out an appropriate course of action, and use reasoning skills to derive general principles.[2]This review is focused on the use of artificial intelligence in the field of dentomaxillofacial radiology.